1996
DOI: 10.1093/oxfordjournals.annonc.a010715
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tamoxifen and hormone replacement therapy on serum cholesterol, bone mineral density and coagulation factors in healthy postmenopausal women participating in a randomised, controlled tamoxifen prevention study

Abstract: We conclude that there were no significant adverse intereactions with tamoxifen and HRT in this small series of patients. The combination results in a reduction of serum cholesterol, increase in BMD especially in the femur and appears not to have any adverse effect on coagulation factors. Multicentre studies should be conducted to evaluate the effect of this combination on relieving menopausal symptoms, disease relapse and overall survival in women who have received treatment for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 21 publications
3
38
0
1
Order By: Relevance
“…Our findings confirm and strengthen the interpretation of prior reports of lower fibrinogen and cholesterol with tamoxifen [2][3][4][5][6]32 and its analogue droloxifene 33 and provide new information concerning C-reactive protein. When the population of women eligible for tamoxifen for the prevention of breast cancer is considered, relevant features of the present study compared with prior studies are as follows: exclusion of women with cancer, 2,32 prohibition of postmenopausal hormone use concurrent with study medication, 4,6 sufficient power, 4,34 and a double-blind control group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings confirm and strengthen the interpretation of prior reports of lower fibrinogen and cholesterol with tamoxifen [2][3][4][5][6]32 and its analogue droloxifene 33 and provide new information concerning C-reactive protein. When the population of women eligible for tamoxifen for the prevention of breast cancer is considered, relevant features of the present study compared with prior studies are as follows: exclusion of women with cancer, 2,32 prohibition of postmenopausal hormone use concurrent with study medication, 4,6 sufficient power, 4,34 and a double-blind control group.…”
Section: Discussionsupporting
confidence: 90%
“…1 Similar to postmenopausal hormone therapy, tamoxifen was predicted to reduce cardiovascular risk on the basis of its lipid-lowering properties. [2][3][4][5][6] Indeed, 3 trials of breast cancer patients have reported 15% to 60% reductions in cardiac death in women treated with tamoxifen. [7][8][9] In the P-1 trial, myocardial infarction rates comparing tamoxifen and placebo did not differ.…”
mentioning
confidence: 99%
“…Since both drugs have similar effects on bone metabolism and turnover, there is a clear AI class effect on bone health in postmenopausal women with hormone-sensitive breast cancer. Tamoxifen has been reported to have some beneficial effects on bone turnover and fracture risk in AI aromatase inhibitor, CI confidence interval, PINP procollagen type I N terminal propeptide, sCTX serum C-terminal telopeptides, uNTX urinary N-terminal telopeptides, ALP alkaline phosphatase postmenopausal women [4,[20][21][22], but the results here show that these positive effects do not carry over once tamoxifen therapy is discontinued. Our study showed an increase in bone turnover that could eventually lead to bone loss.…”
Section: Discussionmentioning
confidence: 61%
“…However, in some, but not all, studies, estrogen replacement, 38,45 tamoxifen, 46,47 and raloxifene 33 also reduced antithrombin III levels, potentially a prothrombotic effect. 48 Only limited data are available concerning the effects of estrogen or SERMs on the activation of the coagulation cascade.…”
Section: Effects Of Serms On Hemostasismentioning
confidence: 99%